Grupo virtual de apoio às mães e pais universitários: relato de experiência - Ribeiro, Kariny dos Santos (Universidade Federal de São Carlos, 2023)
Objective: to describe an experience report on a virtual support group for university mothers and fathers. Method: this is an experience report, from the perspective of an indigenous university mother, through her memories, in the participation in conversation circles and meetings during the informal and virtual meetings formed by a support group in a social network (via facebook), entitled Grupo de Mães e Pais Universitários (GMPU) at a federal university in the interior of São Paulo, during the period from 2014 to 2022. family coexistence center, installation of changing rooms, children's access to the university restaurant. This group played a relevant role in winning some claims, although there are still some outstanding issues. It was found that, in the pandemic period of COVID-19, constant and permanent struggles were impacted by this event, with evasion of participants occurring, due to the completion of graduation course by some mothers and social isolation, which weakened the group's active strength. . Final considerations: it is concluded that in addition to the pandemic episode that made it difficult to implement the group, the university is not prepared to receive mothers with their young children. The importance of the group's return is emphasized, as it is a reference for the next university mothers who need a support network in the academic context and after the first waves of COVID-19.
Virtual support group for university mothers and fathers: experience report
Keywords: Mães; Narrativa pessoal; Povos indígenas; Apoio social; Pandemias; Personal narrative; Mothers; Pandemics; Indigenous peoples; Social support; CIENCIAS DA SAUDE::ENFERMAGEM